PENGARUH PREVENTIVE MAINTENANCE DAN CORRECTIVE MAINTENANCE TERHADAP RELIABILITY MAINTENANCE PADA MESIN POMPA PCM DAN HK PDAM TIRTA SIAK PEKANBARU - Sitorus Pardamean; Daulay Nauli Iwan; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research was conducted on PCM and HK PDAM Tirta Siak Pekanbarumachines, which aims to determine the effect of preventive maintenance and correctivemaintenance on reliability maintenance. This research is a quantitative researchconducted on PDAM Tirta Siak Pekanbaru. The primary data of this study were datacollected using a questionnaire with a Likert scale. The results of the data were processedusing SPSS for further analysis descriptively, and multiple linear regression analysis todetermine the results of the research. 33 samples were selected by the Saturated samplemethod The results of this study indicate that preventive maintenance has an effect onreliability maintenance at PDAM Tirta Siak Pekanbaru. Corrective maintenance has aneffect on reliability maintenance at PDAM Tirta Siak Pekanbaru. Keywords: Preventive, Corrective, Reliability, Maintenance